In Search of Liquidity: Block Trades in the Upstairs and Downstairs Markets - Madhavan, Ananth; Cheng, Minder (Review of Financial Studies, 1997)
We analyze the ability of various market mechanisms to provide liquidity for large equity trades. Using data on 21,077 block transactions in Dow Jones stocks, we find that the “downstairs” NYSE floor market is a significant source of liquidity. Although negotiation in the informal “upstairs” market provides better execution than the downstairs market for large trades, these differences are economically small. We find, however, that upstairs markets are used by traders who can credibly signal that their trades are liquidity motivated. Thus, upstairs markets allow trades that may not otherwise occur.